Wonders of glass: synthesis, elasticity and application - Ab. Aziz, Sidek (Universiti Putra Malaysia Press, 2011)
The term ‘glass’ has a precise scientific meaning: a glass, or a substance in the glassy or vitreous state, is a material, formed by cooling down from the normal liquid state, which has shown no discontinuous change (such as crystallization or separation into more than one phase) at any temperature, but has become more or less rigid through a progressive increase in its viscosity. In common usage, the term ‘glass’ refers to a class of versatile materials of great practical usefulness, with a number of very characteristic properties which are typically hard and brittle solids, lustrous and often optically transparent. Glass is one type of amorphous solid material which also shows property of softening progressively and continuously when heated. The term is usually applied to inorganic solids and not to plastics or other organics. Glasses do not have crystalline (non-crystalline) internal structure. Its molecules have a disordered arrangement, but there is enough cohesion to produce rigidity. Majority of glass seen in everyday life is transparent, but glass can also be translucent or opaque. In science, however, the term glass is usually defined in a much wider sense, including every solid that possesses a non-crystalline (i.e. amorphous) structure and that exhibits a glass transition when heated towards the liquid state. The term ‘glass’ was developed in the late Roman Empire. It was in the Roman glassmaking center at Trier, now in modern Germany, that the late-Latin term glesum originated, probably from a Germanic word for a transparent, lustrous substance. Glasses can be made of quite different classes of materials. Glassy state, which is a universal property of supercooled liquids if they are cooled rapidly enough, is regarded as the fourth state of matter. The physics of glass is the science of the glassy or amorphous state of matter as seen from an atomic or molecular point of view. The mysterious glass transition phenomenon, which connects the liquid and glassy states, is related widely to daily life, industry, materials preparation and a lot of natural phenomena. However, the exact and comprehensive physical understanding of the glass nature is considered to be one of the most challenging problems in condensed matter physics and material science. Due to their random disordered structure, the characterization of glasses is very difficult, and this leads to problems in understanding the formation, nature, and the structure-properties relationship of glasses. The mechanics of solids, regarded as continuous media, forms the content of the theory of elasticity. The macroscopic behaviour of a solid is described by a continuum field theory, the theory of elasticity, which describes the way a solid deforms when stresses are applied. Glass itself provides plentiful precise knowledge of fundamental parameters of elastic modulus, which offer a benchmark reference point for understanding and applications of these materials. In general, the elastic constants of glasses show a correlation with a weighted average of the elastic constants of the constituent elements. This information can be employed in selecting the constituent elements with suitable elasticity for controlling the elastic properties and glass-forming ability of the glasses, and thus the results would enable the design, control and tuning of the formation and properties of any type of glasses. So far glass structure is still the basic foundation in understanding the behaviour of the material. Elasticity of any solid materials can be studied through ultrasonic investigation which is associated with the velocity of ultrasonic waves and bulk density. Hence the elastic moduli are particularly suitable for characterizing glasses as a function of composition. Elastic properties also provide vital information about the structure of solids and they are directly related to inter-atomic potentials. Glass is normally lustrous and transparent in appearance and shows great durability when exposed to natural elements. Hence, glass applications are found to be common and varied in many implementations in human civilization and life, such as domestic appliances, construction elements, scientific investigation, medical devices and artistic items. Throughout history, glass has been used to make ornamental and decorative objects. In addition, it has been used for useful objects such as windows, containers, optical lenses and glass fibers. Its flexible character allows it to be shaped into a wide variety of forms and sizes, in addition to which glass’s cohesiveness with other substance gives benefits in the form or new transitions. The varied applications are driven by one or several of the properties that make the use of glass so attractive. This lecture comprehensively reviews the science of glass and the development of the study of the elastic properties of borate, phosphate and tellurite based glass systems, the establishment of correlations between elastic moduli and other physical properties of glass, and also the application and preparation techniques of glass. The goal is to show the key roles of elastic moduli in the study, formation, and understanding of several types of glasses, and to present a comprehensive elastic perspective on the major fundamental issues from its processing to structure to properties in this rapidly evolving field.